Antioxidant Properties of Various Yacon Leaf Water Extracts and Physicochemical Profile of Decoction During Refrigerated Storage - Wicaksana, Firman; Hartanti, Dwi; Hamad, Alwani (Universitas Airlangga, 2024)
Background: Yacon (Smallanthus sonchifolius (Poepp.) H.Rob.) leaves show promising antioxidant properties, and have traditionally been used for diabetes management in Baturraden, Banyumas, Central Java, Indonesia. This study evaluated the effects of traditional extraction methods and crude drug-to-solvent ratios on the content and activity of antioxidants and physicochemical properties of yacon leaf water extracts during storage. Methods: Crude drugs were extracted by infusion, short-time decoction, and longer-time decoction at ratios of 1:10, 1:20, and 1:100 (w/v). Antioxidant content was analyzed using standard total flavonoid content (TFC) and total phenolic content (TPC). The antioxidant activity was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity and ferric-reducing antioxidant power (FRAP) assays. Yacon leaf water extracts at a ratio of 1:20 (w/v) were stored in tightly closed bottles at 4±2°C for 26 days. The organoleptic characteristics, color, pH, TFC, TPC, and DPPH scavenging activity were evaluated on days 0,1, 3, 6, 12, 18, and 26. Results: The different methods and crude drug-to-water ratios generated different antioxidant activities and contents of the yacon extracts. Yacon leaf decoction for 15 min in a ratio of 1:20 (w/v) produced extract with the best scavenging activity (450.27±5.48 mM Trolox equivalent (TE)/100 g dry weight (DW)), TFC (6.43±0.18 mg Quercetin equivalent (QE)/g DW), and TPC (3.91±0.04 mg gallic acid equivalent (GAE)/g DW). The yacon leaf decoction started to undergo aroma and PH changes on days 3 and 6, respectively. On day 12, the TFC, TPC, and DPPH SA of yacon leaf decoction remained 93.93±3.70, 96.52±1.81, and 89.99±0.91% of the freshly prepared extract, respectively. Conclusion: Our results suggest that extraction using the decoction method for 15 min at a water-to-crude drug ratio of 1:20 (w/v) generated an extract with the best antioxidant profile, which chemically started to change on day 12 during refrigerated storage.